2012
DOI: 10.1155/2012/454195
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Community Mobility for Assistive Technology Users

Abstract: Mobility is frequently described in terms of individual body function and structures however contemporary views of disability also recognise the role of environment in creating disability. Aim. To identify consumer perspectives regarding barriers and facilitators to optimal mobility for a heterogeneous population of impaired Victorians who use assistive technology in their daily lives. Method. An accessible survey investigated the impact of supports or facilitators upon actual and desired life outcomes and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Consistent with the findings of a survey conducted in the USA by Carlson and Berlan [37] with people with disabilities, lack of funding was a barrier to access AT devices. Under-resourcing of government equipment provision schemes has also been identified in Australia as a barrier for AT [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of a survey conducted in the USA by Carlson and Berlan [37] with people with disabilities, lack of funding was a barrier to access AT devices. Under-resourcing of government equipment provision schemes has also been identified in Australia as a barrier for AT [38]. …”
Section: Discussionmentioning
confidence: 99%
“…AT adoption is particularly important to the sustained independence of older adults, increasing the feeling of autonomy compared to reliance on a formal or informal caregiver. For older adults with impairments, AT has been proven to have great potential in enabling activity, increasing safety, and improving access to society and the community 46,47,[56][57][58] . One of the key characteristics of these technologies is their ability to be customizable to the individual seeking to use them.…”
Section: Assistive Technology Acceptancementioning
confidence: 99%
“…On the other hand, some other studies have shown different barriers; help in home for Americans (Dijkers et al, 2002), unavailability of services and policy barriers (Nobakht et al, 2011), unavailability of technology, especially, aid instruments (Layton, 2012). Different population, methodology and statistical approaches in research plus social‚ cultural and economical differences might produce this dissimilarity.…”
Section: Variablesmentioning
confidence: 99%
“…Other studies have demonstrated that natural and transportation barriers have the most effect on disability (Ephraim et al, 2006;Han et al, 2005;Leff, Stallones, Xiang, & Whiteneck, 2010;Keysor et al, 2010;Nobakht, Rassafiani, & Rezasoltani, 2011;Whiteneck et al, 2004). A few studies have shown different barriers such as the unavailability of services, and policy barriers (Nobakht et al, 2011), unavailability of technology, especially, aid instruments (Layton, 2012), and attitude and support barriers (Nichols, Tchounwou, Mena, & Sarpong, 2009). …”
Section: Introductionmentioning
confidence: 99%